The application of nano-hydrogels and hydrogels in wound dressings: Nanohydrogels and hydrogels in wound dressings - Ghorbani, Masoumeh; Ghorbani, Fatemeh; Kahrizi, Sepehr; Naderi-Manesh, Hossein; Kahrizi, Danial (Cellular and Molecular Biology, 2023)
Wounds and the healing process are one of the main concerns of medical science today. A wound is any loss of integrity, or rupture of the layers of skin (epidermis, dermis, and hypodermis) or subcutaneous tissue caused by physical factors (surgical incision, trauma, pressure, and gunshot wounds) or chemical factors (acid burns). It is observed that soft tissue, muscle, or bone is involved in occurrences of wounds. Lesions and fractures of the skin surface necessitate medical attention, wherein dressings expedite the healing process by establishing a physical barrier between the wound and the external environment, thereby preventing further injury or infection. Hydrogel dressings create a moist environment that facilitates common healing steps, such as granulation hyperplasia, epidermal repair, and removal of excess dead tissue. The limited adhesion of the hydrogel and the hydrated wound bed allows for easy removal of the dressing without secondary damage, thereby significantly reducing the discomfort and risk of infection during dressing changes. These modern, wet dressings foster a moist healing environment by absorbing excess inflammatory secretions and allowing proper passage of steam and air, which expedites the healing process. In this analysis, the utilization of hydrogels as wound dressings is briefly presented.